2020
DOI: 10.1080/17482631.2020.1757336
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy among general practitioners in Southern France and their reluctant trust in the health authorities

Abstract: Purpose: Vaccine hesitancy is common in France, including among general practitioners (GPs). We aimed to understand vaccine hesitant GPs' views towards vaccines. Method: We conducted in-depth interviews that were thematically analysed. Result: We found that, facilitated by health scandals and vaccine controversies-that according to participants were not effectively handled by health authorities-the implicit contract existing between health authorities and GPs has been ruptured. This contract implies that healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 46 publications
(54 reference statements)
1
45
1
1
Order By: Relevance
“…These differences were at least partly expected on account of the different degree of penetrance of COVID-19 vaccine among healthcare workers, which was reported as significantly lower in France, in particular in Paris 18 , 19 , 20 , than in Italy. In fact, in 2016, France and Italy were the two countries with the highest rates of vaccine safety skepticism 21 A European study conducted in April 2020 in seven countries showed that France had the largest proportion of the population opposed to a COVID-19 vaccine (10%) and the largest group of people who had not decided whether or not they would be vaccinated (28%).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These differences were at least partly expected on account of the different degree of penetrance of COVID-19 vaccine among healthcare workers, which was reported as significantly lower in France, in particular in Paris 18 , 19 , 20 , than in Italy. In fact, in 2016, France and Italy were the two countries with the highest rates of vaccine safety skepticism 21 A European study conducted in April 2020 in seven countries showed that France had the largest proportion of the population opposed to a COVID-19 vaccine (10%) and the largest group of people who had not decided whether or not they would be vaccinated (28%).…”
Section: Discussionmentioning
confidence: 90%
“…In this regard, while we agree that from an ethical point of view, information campaigns are important for supporting choices, we have come to think that they may be less relevant than confidence in the role of science, a term that was chosen to indirectly allude to the medical community. Lack of confidence in the healthcare system was in fact identified as a major determinant of vaccine hesitancy in the case of COVID-19 and of other vaccines 10 , 19 , 26 , 27 , 28 , and the low vaccine acceptance of healthcare workers in some “difficult” settings may also be evidence of this attitude.…”
Section: Discussionmentioning
confidence: 99%
“…However, several challenges face the GVAP goal to increase the voluntary vaccination against influenza, particularly vaccine hesitancy. This has been faced with almost all vaccines before, such as diphtheria-tetanus-pertussis and hemophilus influenza [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Even in light of the recent COVID-19 pandemic, many remain skeptical and intend to abstain from voluntary vaccinations based upon myths, misinformation, and/or safety concerns [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…From Table A1 we knew that the most trusted source of information was a general practitioner, a doctor, or a pediatrician (79.1% of the total responses). Several investigations showed that a significant share of health care providers is vaccine-hesitant [51][52][53][54][55]. Even though few health care providers are openly against vaccines, many of them find conversations about vaccines with vaccine-hesitant people to be difficult and unproductive [52].…”
Section: Discussionmentioning
confidence: 99%